Effects of Vernonia amygdalina methanol leaf extract and fractions on Ascaridia galli in experimentally infected birds with regard to its pathological effect - Gasaliyu, Khadijat Abidemi (2023)
Helminthiasis, usually a chronic problem in poultry, is the major cause of economic losses in the poultry industry. This study was undertaken with the aim of evaluating the in vitro and in vivo anthelmintic effects of Vernonia amygdalina methanol leaf extract and fractions on Ascaridia galli in experimentally infected birds. Standard protocols for extraction, phytochemical screening, isolation and infection of parasite and histological examination were followed.